The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1038/s41598-017-15932-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal glycemia and weight status on offspring birth measures and BMI-z among Chinese population in the first year

Abstract: To investigate the effects of maternal fasting plasma glucose (FPG) and pre-pregnancy weight status (PPWS) on offspring birth measures and body mass index z-score (BMI-z) in the first year, we conducted a prospective study of 1,096 mother-infant dyads in Guangdong, China, 2014–2015. Multivariate logistic regression was used to test independent/interaction associations of maternal FPG and PPWS with macrosomia/large for gestational age (LGA). Association of PPWS and FPG with offspring BMI-z in the first year was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
3
1
Order By: Relevance
“…The same effect could be behind the negative association found between estimated fetal weight in early pregnancy and the high glucose group trajectory in the present study. In other studies, a positive association between glucose levels and birth weight has been observed 28 , 29 ; however in our study no differences in birth weight were found between glucose groups. This could be explained by the absence of hyperglycemia in any participant and the exclusion of women developing gestational diabetes during follow-up.…”
Section: Discussioncontrasting
confidence: 86%
“…The same effect could be behind the negative association found between estimated fetal weight in early pregnancy and the high glucose group trajectory in the present study. In other studies, a positive association between glucose levels and birth weight has been observed 28 , 29 ; however in our study no differences in birth weight were found between glucose groups. This could be explained by the absence of hyperglycemia in any participant and the exclusion of women developing gestational diabetes during follow-up.…”
Section: Discussioncontrasting
confidence: 86%
“…Another cohort study continuously measured maternal glucose levels and found that a 1-unit increase in maternal mean nighttime glycemia was associated with a 6.0 (95%CI: 0.4, 11.5) percentage-point increase in birth weight percentile [23]. Meanwhile, a prospective study conducted in Guangdong found that for every 1 mmol/L increase in FPG, the risk of LGA and macrosomia increased by 2.01 (95%CI: 1.54, 5.88) and 2.74 (95%CI: 1.85, 7.60), respectively [24]. A regression discontinuity analysis in England [25] found for each 1 mmol/L increase in FPG that the observed increase in birth weight Z score increased by 0.48 (95%CI: 0.39, 0.57) and the odds ratio of LGA increased by 2.61 times (95%CI: 1.86, 3.66).…”
Section: Adjustedmentioning
confidence: 99%
“…Data from various disparate populations also suggests that the combination of these two independent risk factors, maternal hyperglycaemia and maternal obesity, has additive effects on the risk of childhood adiposity and childhood BMI [ 29 31 ].…”
Section: Evidence From Human Cohorts For the Influence Of The Intraut...mentioning
confidence: 99%